(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Pitavastatin (PTV) is a potent lipid lowering drug that acts on hepatocytes by blocking the 3-hydroxy-3- methylglutaryl-CoA reductase enzyme. As a Biopharmaceutical Classification System (BCS) Class II drug, PTV possesses very low water solubility; hence, poor bioavailability leads to poor drug delivery to the target organ. The study aims to develop various PTV solid dispersion (SD) formulations and to investigate the release profile of PTV SD systems. Different PTV physical mixing and SD formulations were prepared using polyvinylpyrrolidone (Kollidon®90F) and Kollicoat®IR hydrophilic polymers by fusion and solvent evaporation approaches. The efficacy of the formulations was evaluated by in vitro PTV release studies. Subsequently, the characterization of SD formulations was performed using thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The in vitro release studies confirmed that all the developed formulations showed a comparatively better release percentage (75.31–98.45%) than the pure PTV (61.76%) after 60 min. Additionally, the outcomes showed that raising the concentration of both polymers improved PTV’s ability to dissolve. In comparison to physical mixing formulations, SD formulations made using fusion and solvent evaporation processes performed better during dissolution. The TGA, DSC, and FTIR studies confirmed that the tested SD formulations (1:2, 1:3 ratios) were stable at high temperatures with a reduction in crystallinity and no notable interaction between the drug and polymers. The SEM analysis showed that the PTV was evenly spread out in the carriers and that the crystal-like structure of the PTV had changed into an amorphous form. Bangladesh Pharmaceutical Journal 27(1): 37-50, 2024 (January)